АМЕТ ВА АЙИМХАН ШАМУРАТОВАЛАР УЙ-МУЗЕЙИ ТАРИХИ - Хужаниязов, У. (SCIENCE and SOCIETY, 2024)
This article describes the history of the house-museum of Amet and Ayimkhan Shamuratov, created in the city of Nukus during the years of independence.